Respuesta :

Answer:

f(-1)=

[tex] \frac{ - 2}{3} [/tex]

f(2)=

[tex] \frac{1}{3} [/tex]

Step-by-step explanation:

let f(x)=f(-1)

but f(x) =3x+1

substituting it into the equation

3x+1=-1

3x=-1-1

3x=-2

dividing through by 3

[tex] \frac{3x}{3} = \frac{ - 2}{3} [/tex]

[tex]x = \frac{ - 2}{3} [/tex]

f(-1) =

[tex] \frac{ - 2}{3} [/tex]

f(2)

let f( x )=f(2)

then

3x+1=2

3x=2-1

3x=1

dividing through by 3

[tex] \frac{3x}{3} = \frac{1}{3} [/tex]

[tex] x = \frac{1}{3} [/tex]

f(2)=

[tex] \frac{1}{3} [/tex]